2018
DOI: 10.3389/fphys.2018.00123
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Photobiomodulation of 808 nm Diode Laser Therapy at Higher Fluence on the in Vitro Osteogenic Differentiation of Bone Marrow Stromal Cells

Abstract: The literature has supported the concept of mesenchymal stromal cells (MSCs) in bone regeneration as one of the most important applications in oro-maxillofacial reconstructions. However, the fate of the transplanted cells and their effects on the clinical outcome is still uncertain. Photobiomodulation (PBM) plays an important role in the acceleration of tissue regeneration and potential repair. The aim of this in vitro study is to evaluate the effectiveness of PBM with 808 nm diode laser therapy, using a flat-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 52 publications
5
46
0
Order By: Relevance
“…Irradiation utilized a laser setup with the following key parameters : 808‐nm wavelength, 1 W of power, 1 W/cm 2 irradiance in CW (pulse energy of 0 Hz) and a single exposure time of 60 s time to generate an outgoing final fluence ( energy density ) of 60 J/cm 2 . The energy parameter used in our work is in line with our previous results that shown as an 808 nm, 1 W, 1 W/cm 2 , 60 s is able to induce PBM in eukaryotic cells, from protozoa and invertebrates up to mammal mitochondria and stem cells . In addition, the wavelength used is in the range of wavelength that is supposed to have a role in the cell‐to‐cell communication by biophotons .…”
Section: Methodssupporting
confidence: 82%
“…Irradiation utilized a laser setup with the following key parameters : 808‐nm wavelength, 1 W of power, 1 W/cm 2 irradiance in CW (pulse energy of 0 Hz) and a single exposure time of 60 s time to generate an outgoing final fluence ( energy density ) of 60 J/cm 2 . The energy parameter used in our work is in line with our previous results that shown as an 808 nm, 1 W, 1 W/cm 2 , 60 s is able to induce PBM in eukaryotic cells, from protozoa and invertebrates up to mammal mitochondria and stem cells . In addition, the wavelength used is in the range of wavelength that is supposed to have a role in the cell‐to‐cell communication by biophotons .…”
Section: Methodssupporting
confidence: 82%
“…Taking into consideration the results showing the increase of vinculin expression aggregation and calcium deposits in both osteoblasts and hMSCs and of Runx-2 expression in osteoblasts after irradiation with 808 nm, our study seems also to suggest that PBM with 808 nm could positively influence osteogenic differentiation of these two types of progenitor cells, as proposed by other research groups [ 71 , 72 , 73 , 74 , 75 , 76 ]. Along these lines, it has also been reported that PBM using NIR light (810 nm and 980 nm) encourages osteoblastic differentiation of hASCs [ 16 , 77 ].…”
Section: Discussionsupporting
confidence: 73%
“…In this study, the reduction of the pro-inflammatory factors (IL6, IL17) and the increase of anti-inflammatory cytokines (IL-10 and IL-1) were observed. 41 The low-power laser 808 nm, 4 J/cm 2 had no effect on the proliferation and differentiation of the MSCs into the osteoblasts and osteoclast cells. 42 Lowpower lasers (15 Hz, 150 mJ, 2.25 W) can proliferate and differentiate the bone marrow MSCs into the osteoblasts cells in 3-dimensional collagen scaffolds that can be used in the treatment of periodontal diseases.…”
Section: Bone Marrow Mesenchymal Stem Cellsmentioning
confidence: 93%